Development of The Web-Based Stacko Media for Beginner-Level BIPA Learners’ Speaking Skills at Unesa - Lusiana Rahman (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2026)
This study is motivated by the increasing interest in BIPA (Indonesian for Foreign Speakers) learning along with the growing need for communication. This condition demands innovation in learning media that can effectively and engagingly support the learning process. Therefore, practical BIPA learning media are needed to support a flexible learning process for beginner-level learners. This study aims to (1) describe the development process of a web-based stacko media for speaking skills of beginner-level BIPA learners, (2) determine the feasibility of the web-based stacko media, and (3) examine the practicality of the web-based stacko media in improving speaking skills of beginner-level BIPA learners. This research employs the 4D development model, limited to the development stage. Data collection instruments include interviews and questionnaires. The results show that the web-based stacko media was developed through the define, design, and develop stages. The feasibility of the media based on expert validation shows that material experts gave a score of 77% (feasible), media experts 96% (very feasible), and language experts 95% (very feasible). The practicality of the media reached 85% from learners and 86% from instructors, both categorized as very practical. Therefore, the web-based stacko media is feasible and practical to be used as a learning medium to improve the speaking skills of beginner-level BIPA learners.